Potentialities of LL37 for Wound Healing Applications: Study of Its Activity in Synergy with Biodegradable Composites Made of PVA and CA - Felgueiras, Helena Prado (2020)
Wound healing is a dynamic and complex process that results from the interaction between cytokines, growth factors, blood components and the extracellular matrix. Conventional dressings made of natural or synthetic materials have only the ability to manage the wound and protect it from repeated trauma. With the advancement of technology, wound dressings have evolved and are now capable of intervening in the healing process by targeting specific features of the wound, aside from protecting the wounded site. In this work, bioactive dressings capable of promoting healing and fighting infection in chronic wounds were explored. Various antimicrobial biomolecules were examined in light of their pathogen fighting skills and immunoregulatory potentialities. Dressing production processes were also investigated. Biodegradable composite dressings made of poly(vinyl alcohol), polycaprolactone, chitosan and cellulose blends were our main focus. The goal was to evaluate the synergistic effect of biomolecules and biodegradable polymeric dressings, considering the local and systemic treatment demands of chronic wounds.